Golden dawn - Kostigen, Thomas (Forge, 2012)
When journalist Michael Shea discovers a plot to smuggle nuclear materials into Iran, he must flee the Iranian secret service with the assistance of Neda Ghazali, a member of an ancient sect that guards a secret prophecy about the end times.